ANALISA PENGARUH ETIKA PROFESI DALAM PENINGKATAN LABA RUGI: (Di UMKM Rumah Jamur Alam Lestari) - Rizkymarshanda Putri Arifin; Rika Yuliastuti (PUTRA JAWA PUBLISHER, 2024)
Micro, small, and medium enterprises play a crucial role in addressing economic challenges within the community. These enterprises often encounter various obstacles in their operations, including navigating through economic systems to manage issues such as profitability and losses. Adhering to professional ethics is essential, and it involves careful consideration of ethical guidelines. This article employs a qualitative research method, specifically a literature review study approach, to analyze the impact of professional ethics on the financial performance of micro, small, and medium enterprises. It is imperative for all economic actors to integrate professional ethics and business ethics into their business practices. The findings of this study underscore the significance of upholding professional ethics as a means to foster a new level of consciousness in business operations. Business ethics are instrumental in ensuring that ethical employees contribute to the success of the company. The application of professional ethics demonstrates a positive influence on the financial outcomes of micro, small, and medium enterprises.